x(4x-3)+x(2x-3)=(6x+7)(x-2)

Simple and best practice solution for x(4x-3)+x(2x-3)=(6x+7)(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(4x-3)+x(2x-3)=(6x+7)(x-2) equation:


Simplifying
x(4x + -3) + x(2x + -3) = (6x + 7)(x + -2)

Reorder the terms:
x(-3 + 4x) + x(2x + -3) = (6x + 7)(x + -2)
(-3 * x + 4x * x) + x(2x + -3) = (6x + 7)(x + -2)
(-3x + 4x2) + x(2x + -3) = (6x + 7)(x + -2)

Reorder the terms:
-3x + 4x2 + x(-3 + 2x) = (6x + 7)(x + -2)
-3x + 4x2 + (-3 * x + 2x * x) = (6x + 7)(x + -2)
-3x + 4x2 + (-3x + 2x2) = (6x + 7)(x + -2)

Reorder the terms:
-3x + -3x + 4x2 + 2x2 = (6x + 7)(x + -2)

Combine like terms: -3x + -3x = -6x
-6x + 4x2 + 2x2 = (6x + 7)(x + -2)

Combine like terms: 4x2 + 2x2 = 6x2
-6x + 6x2 = (6x + 7)(x + -2)

Reorder the terms:
-6x + 6x2 = (7 + 6x)(x + -2)

Reorder the terms:
-6x + 6x2 = (7 + 6x)(-2 + x)

Multiply (7 + 6x) * (-2 + x)
-6x + 6x2 = (7(-2 + x) + 6x * (-2 + x))
-6x + 6x2 = ((-2 * 7 + x * 7) + 6x * (-2 + x))
-6x + 6x2 = ((-14 + 7x) + 6x * (-2 + x))
-6x + 6x2 = (-14 + 7x + (-2 * 6x + x * 6x))
-6x + 6x2 = (-14 + 7x + (-12x + 6x2))

Combine like terms: 7x + -12x = -5x
-6x + 6x2 = (-14 + -5x + 6x2)

Add '-6x2' to each side of the equation.
-6x + 6x2 + -6x2 = -14 + -5x + 6x2 + -6x2

Combine like terms: 6x2 + -6x2 = 0
-6x + 0 = -14 + -5x + 6x2 + -6x2
-6x = -14 + -5x + 6x2 + -6x2

Combine like terms: 6x2 + -6x2 = 0
-6x = -14 + -5x + 0
-6x = -14 + -5x

Solving
-6x = -14 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-6x + 5x = -14 + -5x + 5x

Combine like terms: -6x + 5x = -1x
-1x = -14 + -5x + 5x

Combine like terms: -5x + 5x = 0
-1x = -14 + 0
-1x = -14

Divide each side by '-1'.
x = 14

Simplifying
x = 14

See similar equations:

| -(2x+2)-1=-x-(x+3) | | -108=12b | | |x|=-3 | | 2(3-x)=-2(x-4) | | 5x-10=2x+35 | | 3y^5+81y^2= | | -125=5x-3(-4x+2) | | 5+3x+4x=19 | | -4y+12y=16 | | 2x-8+3x=5x-4 | | -2x^2+6x+4=y | | -3/2= | | 21X-3=15X+15 | | 3x(x-6)=11+(x-1)(3x-1) | | 3ax-4y=8 | | -1(-5-6x)=4(5x+3) | | 2k+8=-5(k-3) | | n+7=3N-1 | | -0.16p-0.05(5-5p)=0.05(p-3)-0.1 | | 7y+1-2y=26 | | (3x+4)+(4x-11)= | | -6(-2+3a)=-78 | | 20x+5=24-1 | | 2+a/4=3/5 | | 8y+3(y-7)=4(y+2)-4 | | -221=13n | | (4x+5)(9x-6)=0 | | 8n+n=54 | | 7x-71=19x+157 | | 16x^3-8=x-128x^2 | | 378-18X=16X | | -25(x-3)=-225 |

Equations solver categories